Low-Level Laser Therapy for Diabetic Dermopathy in Patients With Type 2 Diabetes: A Placebo-Controlled Pilot Study - Abdelhalim, Nermeen Mohamed; Abdelbasset, Walid Kamal; Alqahtani, Bader Ali; Samhan, Ahmed Fathy (Journal of Lasers in Medical Sciences, 2020)
Introduction: Diabetic dermopathy (DD) is the most common cutaneous diabetes marker. Few studies have targeted DD using low-level laser therapy (LLLT). This pilot study aimed to evaluate the effect of LLLT on DD in patients with type 2 diabetes (T2D). Methods: 12 patients with T2D (9 men, 3 women) and bilateral DD were enrolled in this placebo-controlled pilot study, and their ages ranged 50-65 years. One side was subjected to LLLT, three sessions weekly for one month (LLLT side), while the other side received the same treatment protocol with a laser device switched off as a placebo (placebo side). All patients were instructed to receive skincare for both sides, such as debridement, antibiotic creams, and dressings with betadine solution. The diameter of DD lesion and the cutaneous blood flow of the knees and ankles sites were assessed before and after one month at the end of the intervention. Results: At the baseline, no significant differences existed between LLLT and placebo sides in the DD and skin blood flow at the knee and ankle sites (P > 0.05). Post-intervention, a significant improvement occurred in DD diameter and the skin blood flow of the knee and ankle sites in the LLLT side (P < 0.05), while the placebo side showed a significant improvement only in DD diameter (P < 0.05) and non-significant changes in skin blood flow (P > 0.05). Comparing both sides, all measures significantly favored LLLT. Conclusion: The findings of this study indicate that LLLT has beneficial effects on decreasing DD in T2D patients. Also, it was approved that the short term of LLLT is a safe modality to control DD in T2D patients.